P158 Evaluation Of Vital Capacity Changes In Spinal Injured Patients During Episode Of Sepsis. (10th November 2014) - Nasher, M; Pocock, AC; Ward, T; Bongers, T
Abstract : Introduction: Respiratory complications have been suggested as cause of death in approximately 60% of spinal cord injured patients requiring ventilation after spinal cord injury. 1 The vast majority of these respiratory complications are due to infections i.e. pneumonias. It has been postulated that infections trigger a general inflammatory response which directly affects respiratory muscle strength and worsens respiratory function, which can cause respiratory failure. 2 All patients with a high spinal injury (> T1) or respiratory impairment have their vital capacity (VC) measured routinely at least once daily. We designed a project to assess if significant forced vital capacity (FVC) changes occur in spinal injury patients during an episode of sepsis. Methods: In this retrospective review we collected data from all our spinal injury patients with an episode of sepsis (pneumonia or urinary) between March 2010 and February 2013. Results: A total of 16 episodes were recorded in 14 patients (2 female, 12 male) with an average age of 61.8. Level of spinal cord injury varied from C4-T9 and the majority had ASIA (American Spinal Injury Association) grade A. Of all 16 episodes of sepsis, 6 (37.5%) were diagnosed as pneumonia. 10 (62.5%) were of urinary tract origin with positive urine culture. Blood cultures were positive in 4 cases, negative in 11 and not available in 1. FVC ranged from 4000 ml to 1200 ml. VC changes were more profound with respiratory infection as we observed an average FVC change of 1450 ml (50–77%) for the diagnosis of pneumonia and 862 ml (2.3–58%) for urinary tract infection Conclusions: Systemic infection causes significant changes in vital capacity suggesting direct effect of the inflammatory process on diaphragmatic and respiratory muscle function. These VC changes are more profound with respiratory infection and in our study varied from 50%-77% reduction from the baseline. Reduction in VC is an important sign of clinical deterioration and should be routinely measured in any patient with spinal cord injury to prevent respiratory compromise and respiratory failure. References: Watt J et al . Spinal Cord .2011;49:404–10 Boczkowski J. Am J Respir Crit Care Med .2004;169:662–663